Clinical outcomes and characteristics of P30L mutations in congenital adrenal hyperplasia due to 21-hydroxylase deficiency - Mirjana Kochova; Violeta Anastasovska; Henrik Falhammar (Springer Science and Business Media LLC, 2020)
Despite numerous studies in the field of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency, some clinical variability of the presentation and discrepancies in the genotype/phenotype correlation are still unexplained. Some, but not all, discordant phenotypes caused by mutations with known enzyme activity have been explained by in silico structural changes in the 21-hydroxylase protein. The incidence of P30L mutation varies in different populations and is most frequently found in several Central and Southeast European countries as well as Mexico. Patients carrying P30L mutation present predominantly as non-classical CAH; however, simple virilizing forms are found in up to 50% of patients. Taking into consideration the residual 21-hydroxulase activity present with P30L mutation this is unexpected. Different mechanisms for increased androgenization in patients carrying P30L mutation have been proposed including influence of different residues, accompanying promotor allele variability or mutations, and individual androgene sensitivity. Early diagnosis of patients who would present with SV is important in order to improve outcome. Outcome studies of CAH have confirmed the uniqueness of this mutation such as difficulties in phenotype classification, different fertility, growth, and psychologic issues in comparison with other genotypes. Additional studies of P30L mutation are warranted.